Problem checklist to identify problems with students in Islamic boarding schools - Alifia, Syifa; Fauziah, Fitri; Syaputra, Yogi Damai (Fakultas Dakwah dan Komunikasi UIN Walisongo, 2023)
Purpose - This article aims to analyze the use of DCM (Problem Checklist) to identify student problems in Islamic boarding schools. Second, develop a guidance and counseling service program for Islamic boarding school students' issues.Method - This type of research uses descriptive quantitative analysis. The data collection technique uses the Problem Checklist (DCM) instrument. Data was obtained from 18 students from class XII at the El-Syarief Islamic Boarding School. Data was processed using MS Excel and analyzed using a quantitative description.Result - The research results show that students are very problematic in social and organizational elements, with a percentage of 60%, and personal aspects, with a percentage of 100%. Some guidance and counseling services that can be used to overcome student problems include individual counseling services, group guidance, and information.Implication – This research aims to identify what problems students face in Islamic boarding schools and determine interventions that are appropriate to the issues they face. Counselors in schools and Islamic boarding schools can implement the results of this intervention.Originality - This research strengthens the identification of student problems and designs appropriate interventions to overcome these problems.***Tujuan - Artikel ini bertujuan untuk menganalisis penggunaan DCM (Daftar Cek Masalah) untuk mengidentifikasi masalah santri di pesantren. Kedua, mengembangkan program layanan bimbingan dan konseling untuk permasalahan santri di pondok pesantren.Metode - Jenis penelitian ini menggunakan analisis kuantitatif deskriptif. Teknik pengumpulan data menggunakan instrumen Daftar Cek Masalah (DCM). Data diperoleh dari 18 siswa kelas XII di Pondok Pesantren El-Syarief. Data diolah menggunakan MS Excel dan dianalisis menggunakan deskripsi kuantitatif.Hasil - Hasil penelitian menunjukkan bahwa santri sangat bermasalah pada unsur sosial dan organisasi, dengan persentase 60%, dan aspek pribadi, dengan persentase 100%. Beberapa layanan bimbingan dan konseling yang dapat digunakan untuk mengatasi permasalahan siswa antara lain layanan konseling individu, bimbingan kelompok, dan informasi.Implikasi - Penelitian ini bertujuan untuk mengidentifikasi masalah apa saja yang dihadapi siswa di pondok pesantren dan menentukan intervensi yang sesuai dengan masalah yang mereka hadapi. Konselor di sekolah dan pondok pesantren dapat mengimplementasikan hasil intervensi ini.Orisinalitas - Penelitian ini memperkuat identifikasi masalah santri dan merancang intervensi yang tepat untuk mengatasi masalah tersebut.